SAARC; Sapta to SAFTA - "Gupta, Anshuman" (Delhi, 2002)
The book explores the potentialities of economic cooperation among the countries of the South Asian region under the aegis of South Asian Association of Regional Cooperation (SAARC). It underscores the imperatives of forging a successful Regional Trading Bloc (RTB) in the region in view of the increasing trend in favour of such groupings the world over. It examines at length whether the regionalism and multilateralism under World Trade Organization (WTO) are complementary to each other or contradictory. It critically studies the progress made so far in carrying out the work of opening up the economies under SAARC Preferential Trading Arrangement (SAPTA) and the time and work required to upgrade it into South Asian Free Trade Area (SAFTA). It also draws a comparison between the regional trading blocs among the developed countries, like EU, NAFTA etc., and in South Asia, comprising the developing and least developed countries, in terms of trade cooperation. Finally, it attempts to recommend some measures to step up economic cooperation among the member countries.
Keywords: SAFTA